2022
DOI: 10.3390/ijerph192013443
|View full text |Cite
|
Sign up to set email alerts
|

City-Level Travel Time and Individual Dietary Consumption in Latin American Cities: Results from the SALURBAL Study

Abstract: There is limited empirical evidence on how travel time affects dietary patterns, and even less in Latin American cities (LACs). Using data from 181 LACs, we investigated whether longer travel times at the city level are associated with lower consumption of vegetables and higher consumption of sugar-sweetened beverages and if this association differs by city size. Travel time was measured as the average city-level travel time during peak hours and city-level travel delay time was measured as the average increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…According to Guimares’ research, residents had lower odds of regularly consuming vegetables in cities with higher average travel and delay times, and they have lower odds of regularly consuming sugar-sweetened beverages in areas with higher average delay times [ 2 ]. This research also revealed that these relationships are stronger in bigger cities, where there are more vehicles on the road and people’s activities typically take place at a greater distance from one another.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Guimares’ research, residents had lower odds of regularly consuming vegetables in cities with higher average travel and delay times, and they have lower odds of regularly consuming sugar-sweetened beverages in areas with higher average delay times [ 2 ]. This research also revealed that these relationships are stronger in bigger cities, where there are more vehicles on the road and people’s activities typically take place at a greater distance from one another.…”
mentioning
confidence: 99%
“…This research also revealed that these relationships are stronger in bigger cities, where there are more vehicles on the road and people’s activities typically take place at a greater distance from one another. In turn, the decrease in daily travel time can free up more time to make healthier meals and access foods of higher quality [ 2 ].…”
mentioning
confidence: 99%